Managerial accounting - Warren, Carl S.; Reeve, James M.; Fess, Philip E. (Cincinnati, Ohio : South-Western College, 1999)
This book is about: Analyzing transactions; Matching concept; Adjusting process; ...
Keywords: Accounting; Managerial accounting